2015
DOI: 10.1097/meg.0000000000000461
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of faecal calprotectin in ulcerative colitis patients

Abstract: Our data strongly support the use of FC for staging the activity of disease, predicting relapse and leading decision-making in a UC setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
12
2
Order By: Relevance
“…It can, however, be argued that complete normalization of FC—potentially indicating complete resolution of macroscopic and microscopic inflammation—is a therapeutic target beyond mucosal healing. In support of this, recent studies in adults have shown that even in the absence of endoscopic signs of disease activity, levels of FC are predictive of long-term outcome [ 28 , 20 ]. Furthermore, a therapeutic algorithm based on levels of FC alone did improve medium-term outcome in adults with IBD [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 89%
“…It can, however, be argued that complete normalization of FC—potentially indicating complete resolution of macroscopic and microscopic inflammation—is a therapeutic target beyond mucosal healing. In support of this, recent studies in adults have shown that even in the absence of endoscopic signs of disease activity, levels of FC are predictive of long-term outcome [ 28 , 20 ]. Furthermore, a therapeutic algorithm based on levels of FC alone did improve medium-term outcome in adults with IBD [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 89%
“…Quantification of FC was carried out using CalFast (Eurospital, Trieste, Italy) according to the manufacturer’s protocol. FC values > 150 μg/g were considered predictive of mucosal endoscopic activity as previously demonstrated 53 .…”
Section: Methodsmentioning
confidence: 99%
“…Eligible patients were asymptomatic subjects aged 18–70 years with long-standing (≥ 8 years) UC, in stable clinical remission (simple clinical colitis activity index; SCCAI = 0), and FC levels higher than 150 µg/g 53 . Patients were included in the study after signing the informed written consent.…”
Section: Methodsmentioning
confidence: 99%
“…Active vs inactive disease. Overall, 8 studies only included patients with active disease (Lewis et al, 19 Dhanda et al, 20 Jharap et al, 21 Scaioli et al, 23 Seo et al, 3 Achitei et al, 24 Mirpour et al, 25 Jairath et al 1 ), whereas 15 studies included patients with both active and inactive disease (Bodelier et al, 26 Schoepfer et al, 27 Pagnini et al, 28 Beattie et al, 7 Azzolini et al, 12 Hirai et al, 29 Langhorst et al, 30 Arai et al, 31 Higging et al, 32 Ricanek et al, 33 Samuel et al, 34 Taleban et al, 35 Falvey et al, 36 Chen et al, 37 and Colombel et al 22 ). Unfortunately, the published data do not provide information for active vs inactive disease separately.…”
Section: Association Between Clinical Symptoms and Endoscopy In The Dmentioning
confidence: 99%